A Standard for Human Plasmin - Kirkwood, T. B. L; Campbell, P. J; Gaffney, P. J (Thrombosis and Haemostasis, 1975)
An international collaborative study involving ten laboratories was undertaken to assess the suitability of a preparation of human plasmin in 50% glycerol to serve as a single standard for the bioassay of plasmin activity. The study included examination of the stability of the proposed standard and comparisons between assay methods. The results suggest that the human plasmin preparation coded 72/379 is suitable to serve as a standard. It is sufficiently stable to define the unit of plasmin activity for several years at or below 4° C and for short periods at about 20° C. The preparation has been assigned a potency of 8 units per ml. The International Committee on Thrombosis and Haemostasis (Basle, 1974) has recommended the use of this material as a standard.